Bio-inspired nanomaterials in agriculture and food: Current status, foreseen applications and challenges. (October 2018) - Chaudhry, Niladri; Dwivedi, Sourabh; Chaudhry, Vasvi; Singh, Anuradha; Saquib, Quaiser; Azam, Ameer; Musarrat, Javed
Abstract: Nanotechnology is a potential area that revolutionizes almost every sector of life and is predicted to become a major economic force in the near future. Recently, nanomaterials have received great attention for their properties at nanoscale regime and their applications in many areas primarily, agriculture and food sectors. The Nanomaterials are dispersed or solid particles, with a size range of 1–100 nm. In recent times, there has been an increased research work in this area to synthesize nanomaterials using various approaches. The use of natural biomolecules using 'green' approach play key role in the synthesis of nanomaterials having different shapes and sizes. Further this 'green synthesis' approach not only minimize the cost but also limit the need of hazardous chemicals and stimulates synthesis of greener, safe and environmentally friendly nanoparticles. The present review focus on studies based on the biosynthesis of nanoparticles using biomolecules such as plants, bacteria, fungi, etc. The text summarizes the recent work done globally by renowned researchers in area of biosynthesis of nanomaterials. It also discusses the potential applications of biologically mediated nanomaterials in the areas of agriculture and food and a critical evaluation of challenges within this field. Highlights: Biological nanomaterials received great attention for their properties at nanoscale regime and their applications in agriculture and food sectors. The review imbibes the studies on the biosynthesis of nanoparticles using biomolecules such as plants, bacteria, fungi, etc. It also discusses the potential applications of biologically mediated nanomaterials.